PENGARUH KEPEMILIKAN PEMERINTAH DAN KEPEMILIKAN ASING TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN INFRASTRUKTUR YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Algifari, Isra; Makhdalena, Makhdalena; Riadi, RM (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study aims to determine the effect of government ownership and foreign ownership on debt policy both simultaneously and partially in transportation and infrastructure sector companies that are listed on the Indonesia Stock Exchange (IDX) in the period of 2011 to 2015. The population of this research is all transportation and infrastructure sector companies which was listed on the Indonesia Stock Exchange in the period 2011 to 2015 where the data was examined by census. This study uses secondary data sourced from the company's annual report. The data analysis technique used is multiple linear regression with the help of the SPSS program (Statistical Package for Social Science). The results of the study indicate that government ownership and foreign ownership simultaneously influence debt policy. Government ownership partially has a negative effect on debt policy. While foreign ownership has a negative effect on debt policy.Key Words: Government Ownership, Foreign Ownership, and Debt Policy